Analysis of Fractures and Microstructures on Different Injection Speeds in High-Pressure Die-Casting Magnesium Alloy - Ibrahim, M. D.; Jendia, J.; Kashiwabara, Y.; Roslan, L. B.; Watanabe, H.; Sunami, Y. (International Journal of Integrated Engineering, 2023)
In this study, to clarify the unknown physical properties of the Mg-Al-Th-RE alloy, the relationship between the injection conditions and the internal porosities, and the mechanical properties exerted by the solidification microstructure was investigated. The obtained cast samples were investigated using X-ray CT internal measurements, tensile tests, Vickers hardness tests, and solidification microstructure observations. The tensile strength and the elongation at the injection speed of 5.0 m/s were higher than at 2.0 m/s. The number of porosities affected the tensile strength and the elongation even at the same fracture position. In addition, it was confirmed that segregation affected the destruction smaller the porosity size and the greater the variability of porosity. As the injection speed increased, the amount of heat transferred between the molten metal and the wall surface also increased, resulting in quick freezing and solidification. The tensile strength increased at the injection speed of 5.0 m/s because the interface between the scattered primary crystals and eutectic systems was narrow. On the other hand, at the injection speed of 2.0 m/s, the tensile strength decreased because the molten metal was delayed in solidification and dendrite growth became remarkable.